2004
DOI: 10.1096/fj.04-1506fje
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and cigarette smoke alter chromatin remodeling but differentially regulate NF‐κB activation and proinflammatory cytokine release in alveolar epithelial cells

Abstract: Oxidative stress is implicated in lung inflammation due to its effect on proinflammatory gene transcription. Changes in gene transcription depend on chromatin remodeling and the relative activities of histone acetyltransferases (HATs) and histone deacetylases (HDACs). Alterations in the nuclear histone acetylation:deacetylation balance may result in uncontrolled transcription of specific proinflammatory genes. We studied the effect of hydrogen peroxide (H2O2) and cigarette smoke condensate (CSC) on histone ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
229
2
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(257 citation statements)
references
References 56 publications
15
229
2
5
Order By: Relevance
“…Because D-NAC and non-thiol antioxidants like trolox did not block p65-NFB DNA binding (data not shown), the results indicated that the NAC-mediated effect on p65-NFB was GSH-dependent. These results were also in agreement with recent reports showing that NAC and increased GSH down-regulate cigarette smoke-and tumor necrosis factor-induced NFB activation in A549 alveolar epithelial, U937 human histiocytic lymphoma, HeLa human epithelial, and MCF-7 human breast cancer cells (37,38). Our results also indicate that the NFB pathway is crucial in protecting MIA PaCa-2 cells from hypoxia-induced cell death, as confirmed by the pro-apoptotic effect of the NFB inhibitor (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Because D-NAC and non-thiol antioxidants like trolox did not block p65-NFB DNA binding (data not shown), the results indicated that the NAC-mediated effect on p65-NFB was GSH-dependent. These results were also in agreement with recent reports showing that NAC and increased GSH down-regulate cigarette smoke-and tumor necrosis factor-induced NFB activation in A549 alveolar epithelial, U937 human histiocytic lymphoma, HeLa human epithelial, and MCF-7 human breast cancer cells (37,38). Our results also indicate that the NFB pathway is crucial in protecting MIA PaCa-2 cells from hypoxia-induced cell death, as confirmed by the pro-apoptotic effect of the NFB inhibitor (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The concentration of the complexes that caused 50% inhibition of the growth (IC 50) was determined by using the sulforhodamine-B (SRB) assay (39) as reported (13). For IC 50 determinations on A549 cells with increased thiol levels, cells were preincubated with 5 mM N-acetylcysteine for 2 h, a concentration and time previously reported to be nontoxic for this cell line (40), and confirmed by our controls. The N-acetylcysteine was removed, cells were washed twice in PBS, fresh cell medium was added, and IC 50 values were then determined.…”
Section: Ic 50supporting
confidence: 52%
“…To further explore the dysregulation of inflammatory response in KO mice, modifications of the cell signaling pathway in the lungs were examined. In particular, we found NF-B, a major transcription factor for cytokine production in alveolar epithelial cells, to be highly activated (61).…”
Section: Discussionmentioning
confidence: 83%